Analysis Of Trade Policy On Food Security In Developing Countries - Lestari, Rahayu; Muflihah, Lilih; Lusiana; Aulia, Mumtaza (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Food security represents a multidimensional challenge for developing countries, influenced by global trade dynamics, import dependency, price volatility, and domestic production capacity. This study employs a mixed‑methods approach combining quantitative indicators of food‑trade dependency with qualitative analysis of policy frameworks to examine how trade policies shape food security outcomes. The findings reveal that countries such as Indonesia, the Philippines, and several South Asian and African states experience structural dependence on staple food imports—including rice, wheat, maize, and soybeans—creating vulnerabilities during global price shocks and export restrictions. Conversely, leading exporters such as India, Thailand, and Vietnam demonstrate how strategic agricultural development, productivity enhancement, and export‑management policies can strengthen both domestic availability and global market positioning. The study concludes that trade policies must balance market openness with domestic capacity‑building to enhance long‑term food security resilience.